2021
DOI: 10.2147/jpr.s276941
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Polydioxanone Thread Embedding Acupuncture Compared to Physical Therapy in the Treatment of Patients with Non-Specific Chronic Neck Pain: An Assessor-Blinded, Randomized, Controlled, Clinical Trial

Abstract: Background Thread embedding acupuncture (TEA) has recently been used as a conservative treatment method for non-specific chronic neck pain (CNP). The objective of this study was to evaluate the effectiveness and safety of TEA compared to physical therapy (PT) for treating patients with CNP. Methods A total of 128 patients diagnosed with CNP were randomly assigned to a TEA group and a PT group at a 1:1 ratio. The TEA group received four sessions of TEA, while the PT grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Kim et al 15 and Chu et al 16 conducted RCTs and reported that TEA was not associated with serious side effects of TEA and that it significantly improved the quality of life of patients. Kim et al 26 reported that there was a significant improvement of pain relief in TEA compared to that with conventional physical therapy. However, they reported one case of pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 15 and Chu et al 16 conducted RCTs and reported that TEA was not associated with serious side effects of TEA and that it significantly improved the quality of life of patients. Kim et al 26 reported that there was a significant improvement of pain relief in TEA compared to that with conventional physical therapy. However, they reported one case of pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when designing TEA clinical trials, the proportion of individualized embedding points could be increased using the acupoint pool, which the practitioners chose according to the patient's symptoms, and reduce the number of fixed embedding points to obtain an appropriate level of stimulation. This strategy was confirmed by the proportion of patients who reported AEs, which was reduced from 22.6% to 17.2% [25].…”
Section: Discussionmentioning
confidence: 83%
“…The musculoskeletal conditions/diseases in the included 22 clinical studies were lumbar disc herniation (5 studies, 22.7%) [12][13][14][15][16], cervical spondylotic radiculopathy (4 studies, 18.2%) [17][18][19][20], chronic low back pain (3 studies, 13.6%) [21][22][23], chronic neck pain (3 studies, 13.6%) [24][25][26], ankylosing spondylitis (2 studies, 9.1%) [27,28], rheumatoid arthritis (2 studies, 9.1%) [29,30], and other conditions/diseases (3 studies, 13.6% each) such as acute adhesive capsulitis [31], primary restless legs syndrome [32], and Duchenne muscular dystrophy [33]. There were 10 studies in which TEA was applied as a single intervention in the experimental group, and 11 studies in which TEA was used in a combined intervention, such as adjuvant or synergistic therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these improvements in safety, TEA has been used for the treatment of a wide range of diseases including obesity, rhinitis, facial paralysis, 15 and several conditions of musculoskeletal pain. [16][17][18][19] Furthermore, for the purposes of long-term pain management and functional improvement, many studies on TEA treatment for shoulder diseases have shown considerable clinical effects for frozen shoulder, 20 periarthritis, 21 and rotator cuff syndrome; 22 however, there has been no clinical study on the effect of TEA on shoulder instability.…”
Section: Introductionmentioning
confidence: 99%